Komunikasi Persuasif Kader Posyandu Dalam Sosialisai Menu Gizi Seimbang Kepada Ibu Balita - Sari, Dian Nurvita; Winangsih, Rahmi; Permana, Rangga Saptya Mohamad (Community Services and Social Work Bulletin, 2024)
Stunting remains a critical public health issue in Indonesia, prompting nationwide intervention programs involving multi-level stakeholders, including grassroots health volunteers (Posyandu cadres). This study investigates the persuasive communication strategies employed by Posyandu Anggrek II B cadres in Cipondoh, Tangerang, to promote balanced nutrition among mothers of under-five children. Utilizing a qualitative approach through participant observation and in-depth interviews, the research examines the six key elements of persuasive communication: communicator, message, channel, receiver, feedback, and effect. The findings reveal that the cadres effectively delivered culturally contextualized and motivational health messages using public health forums and practical demonstrations of diverse nutritious food menus. Notably, this communication fostered cognitive, affective, and behavioral shifts among mothers, indicating potential long-term impact on stunting prevention. However, challenges such as motivational barriers and semantic misunderstandings due to diverse sociolinguistic backgrounds were also identified. This study underscores the vital role of well-trained community health communicators in behavior change interventions and highlights the necessity of continuous support and adaptive strategies to overcome communication obstacles. By focusing on localized, persuasive engagement, this research contributes empirical evidence to the discourse on sustainable, community-driven public health strategies in the fight against child malnutrition.